O’ZBEK OILALARIDA MAKTABGACHA YOSHDAGI BOLALARDA RUS TILIDA NUTQNI RIVOJLANTIRISH. - Abdulloyeva Anora; Raxmonova Mehriniso (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article examines the features of speech development in preschool children speaking Russian in a bilingual environment typical for Uzbek families. The difficulties faced by children in acquiring Russian as a second language are analyzed and pedagogical methods aimed at the effective development of Russian speech are proposed.